Processing and Mechanical Behaviour of Hybrid Fiber Reinforced Polymer Composite Materials - Naidu, A.Lakshumu; Rao, P. S. V. Ramana (International Journal of Psychosocial Rehabilitation, 2020)
-- The cutting edge dynamic world can't envision its improvement without getting the idea of progression material composite. Different explores are going on in this field to accomplish the ideal standard. Common fiber fortified polymer composite has a tremendous liking to supplant the composite made up of manufactured fiber. This is essentially a direct result of the focal points like light weight, non-poisonous, non- grating, simple accessibility, minimal effort, and biodegradable properties. The manufactured strands have higher part of the arrangement like elasticity and malleable modulus anyway the particular mechanical properties like explicit tractable modulus and other explicit (properties/explicit gravity) of common fiber provides a delightful outcome for composites when contrasted with engineered fiber based composites. The target of the present examination is to research the mechanical properties of short jute and bamboo fiber strengthened epoxy based composites filled with coconut shell ash. Jute and Bamboo strands with various length and substance are fortified in epoxy sap to create hybrid composite materials. The impact of fiber length and substance on the mechanical bheviour of composites is examined.